Calcium Phosphates as Delivery Systems for Bisphosphonates - Bigi, Adriana (J Funct Biomater, 2018)
Bisphosphonates (BPs) are the most utilized drugs for the treatment of osteoporosis, and are usefully employed also for other pathologies characterized by abnormally high bone resorption, including bone metastases. Due to the great affinity of these drugs for calcium ions, calcium phosphates are ideal delivery systems for local administration of BPs to bone, which is aimed to avoid/limit the undesirable side effects of their prolonged systemic use. Direct synthesis in aqueous medium and chemisorptions from solution are the two main routes proposed to synthesize BP functionalized calcium phosphates. The present review overviews the information acquired through the studies on the interaction between bisphosphonate molecules and calcium phosphates. Moreover, particular attention is addressed to some important recent achievements on the applications of BP functionalized calcium phosphates as biomaterials for bone substitution/repair.